Cellular Factors Targeting APCs to Modulate Adaptive T Cell Immunity - Anabelle Visperas; Jeongsu Do; Booki Min (Journal of Immunology Research)
The fate of adaptive T cell immunity is determined by multiple cellular and molecular factors, among which the cytokine milieu plays the most important role in this process. Depending on the cytokines present during the initial T cell activation, T cells become effector cells that produce different effector molecules and execute adaptive immune functions. Studies thus far have primarily focused on defining how these factors control T cell differentiation by targeting T cells themselves. However, other non-T cells, particularly APCs, also express receptors for the factors and are capable of responding to them. In this review, we will discuss how APCs, by responding to those cytokines, influence T cell differentiation and adaptive immunity.